The Effect of Memrise Application Towards Students’ Vocabulary Mastery - Robi Faizal Rohim; Rizdki Elang Gumelar; Riandi Riandi (Journal of English Language Learning, 2022)
The research paper aims to know whether the use of Memrise Application gives a significant effect towards students’ vocabulary mastery at the Eight grade student’ of MTs Mathla’ul Anwar or not. The research paper uses the quantitative research design with the characteristics of experimental method that is design into two classes. They are the experimental and the control class. The population of this research consists of 71 students and the sample of this research is VIII A as experimental class consists 22 Students and VIII B as control class consists 22 students. Total of sample is 44 students. The instrument is a test and data of this research are collected by giving the per-test and post-test. The data is analyzed using statistical of program SPSS 22 including mean, standard deviation, and t-test. It could be seen from the result of the post-test of experimental and control class. Based on the result of data analysis and interpretation of the research. It is clear there is significant effect of Memrise application towards students’ vocabulary mastery at the eighth-grade students’ of MTs Mathla’ul Anwar Malingping. It can be seen the minimum score of pre-tests of experimental class is 44, maximum 88, mean 61.91 and standard deviation 11.880, while the minimum score of post-tests of experimental class is 52, maximum 92, mean 72.82 and standard deviation 12.010. Furthermore, the minimum score of pre-tests of control class is 36, maximum 76, mean 58.73 and standard deviation 9.731, while the minimum score of post-tests of control class is 40, maximum 80, mean 64.64 and standard deviation 9.469. The result of t-test obtained sig. value 0.000 ≤ α = 0.05. Ha is accepted and Ho is rejected. It can be concluded that there is significant effect of Memrise application towards student’s vocabulary mastery.